Limites à indenização punitiva - Gouveia, Roberta Corrêa (2012)
This thesis discusses the possibility of establishing limits on punitive damages that would make them viable if and when adopted in Brazil. Our interest in proposing boundaries comes from an analysis of Brazilian jurisprudence, in which we observed that courts justify the amount of pain and suffering damages awards by applying characteristic elements of punitive damages such as the high degree of reprehensibility of the conduct and the wealth of the defendant but based only on the nature of the injury itself and without well-defined criteria. Through a comparative study we see that Common Law countries apply punitive damages as a legal remedy through which injured persons receive from the defendants, in addition to full compensation for their actual injury, pecuniary amounts based on the willful misconduct or gross negligence of the offender. The adoption of this form of civil penalty would not infringe Brazilian constitutional guarantees and would not constitute unjust enrichment of the victim, because it would restore inner peace to the victim and bring back justice to the victim and society in general after the damaging behavior of the agent. In addition to criminal and administrative sanctions, Brazilian society needs a new punitive instrument, because in Brazil tort law is used to compensate the plaintiff for injury he receives, and is not an efficient means of punishment and deterrence of illicit behavior. Among the subjective limits we propose to punitive damages is a requirement for a high degree of reprehensibility of the wrongdoer s conduct, such as intentional wrongdoing, willful misconduct, gross negligence or some other kind of outrageous conduct. The objective limits are the amount of compensatory damages, the concrete circumstances of the case, the financial situation of the parties and expected profit of the defendant. The payment of punitive damages should be made to the victim and to a public fund, but the percentage may vary according to the case